Urbanização contemporânea face as informalidades no rural: um olhar a partir dos loteamentos clandestinos e irregulares de Uberlândia – MG - Souza, Tatiana Silva (2020)
In Uberlândia, municipality of Minas Gerais – Brazil, especially in the last two decades, the production of illegal real estate developments has intensified - those whose approval, execution or registration in the real estate office is not regular. According to data from “Operação Terra Prometida” (2018), a partnership between the Public Ministry of the State of Minas Gerais, the Environmental Military Police of the State of Minas Gerais and the Municipality of Uberlândia, the municipality has 122 subdivisions in an irregular or illegal situation, both in the Urban and Rural Areas. These factors concern public bodies and distort the City Statute and the Master Plan as their main instrument, as in principle these laws should ensure the social function of the city, property and guarantee the well-being of the population. In addition to legal problems, the expansion and (re)production of these subdivisions significantly compromise the environmental and life quality of those who occupy it, with problems related to the deficiency of urban and rural infrastructure; lack of community facilities and free leisure areas; precarious drinking water supply; lack of sewage services; weakness in the supply of electricity and insufficiency in public transport lines. Thus, the present work aimed to understand the territorial dynamics of the production of clandestine and irregular subdivisions in Uberlândia which can be characterized as a process of urban dispersion and / or periurbanization, in order to consider that this phenomenon, beyond the metropolises, it can also be found in medium-sized cities. The methodology for its development consisted of reading a bibliography on the theme combined with empirical experience through fieldwork in the referred subdivisions. The results demonstrate that, despite the laws and determinations of land use, the space is, in fact, organized by private actions that, selecting areas, carrying out projects and inducing the application of public investments, create differentiated patterns of spatial planning and expansion, which is characterized by the production of congruences and inconsistencies in the space where the public and the private coexist; the formal and the informal; the legal and the illegal; regular and irregular.